Instabilidade financeira no espaço: uma abordagem monetária da dinâmica econômica regional - Teofilo Henrique Pereira de Paula (2009)
This essay takes money as an active factor in the process of regional allocation of productive resources. Nevertheless, it develops an alternative approach to address the problem of determination of liquidity preference over the space. To do this, the introduction of a temporal dimension into the centre-periphery analysis is proposed by arguing that the behavior of the regional liquidity preference, in relation to the intrinsic instability of the economic system, is determined by the region degree of centrality. A fundamental implication of this perspective is that the relationship between liquidity preference and centrality can be represented as a parable concave to the horizontal axis, instead of a downward curve such as suggested by post-keynesian theory. This would be implied basically by a stable sub-optimum equilibrium witch characterize peripheral regions located at extreme of a centre-periphery gradient. At second step the relationship between money and space is analyzed by an agent based-model whose results have presented a close resemblance with a typical minskyan financial crisis. The spatial implications of this behavior was thus analyzed by a spatialized version of the model, with the major finds being summarized as: i) the banks spread is a relevant locational factor by generate, per se, path of concentrations witch emulates stylized facts in regional economics; and ii) financial crisis have distinct effects over the space, contributing to perpetuate the uneven development. On the normative perspective this finds suggest a need to introduce regional differentiated components into monetary policy.